Golgi Pathology in Neurodegenerative Diseases - Catherine Rabouille (Frontiers Research Topics, 2016)
The Golgi apparatus is a central organelle that lies at the heart of the secretory pathway. It ensures post-translational protein modifications such as glycosylation and cleavage as well as protein sorting to neuronal axons and dendrites. Structural and functional alterations of the Golgi apparatus (fragmentation and atrophy), which are collectively termed Golgi pathology, are now recognized as a constant feature of many neuro-degenerative diseases. However, the molecular mechanisms underlying these changes and their precise relevance to neurodegeneration have not yet been completely elucidated. This eBook contains 13 reviews that address the molecular mechanisms of Golgi pathology in Parkinson and Alzheimer diseases, amyotrophic lateral sclerosis (ALS) and spinal muscular atrophies, and discuss their potential relevance to the pathological loss of neuronal cell bodies, axons and synapses.